2022
DOI: 10.1007/s11089-021-00988-9
|View full text |Cite
|
Sign up to set email alerts
|

Relations Among Locus of Control, Religiosity, and Resiliency in Collegiate Football Players

Abstract: Resiliency in athletes is related to effective coping strategies. Expectedly, during the COVID-19 pandemic, this attribute was highlighted in collegiate football players. To date, the relations among locus of control (LOC), strength of religious beliefs (i.e., religiosity), and resiliency in collegiate football players have not been explored in the literature. Exploring the relation of LOC and religious beliefs to resiliency may shed light on avenues to foster resiliency in football players, which in turn can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Religious perceptions and psychological well-being levels of football players who have a strong and moderate perception of religiosity about themselves were found to be higher (Table 5). Slatinsky et al [45] in their work state that football players with greater internal locus of control and higher strength of religious beliefs had a higher level of resiliency than players with higher external LOC and lower strength of religious beliefs. It is also possible to reach other similar studies [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Religious perceptions and psychological well-being levels of football players who have a strong and moderate perception of religiosity about themselves were found to be higher (Table 5). Slatinsky et al [45] in their work state that football players with greater internal locus of control and higher strength of religious beliefs had a higher level of resiliency than players with higher external LOC and lower strength of religious beliefs. It is also possible to reach other similar studies [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Due to human limitations in the face of uncertainties, footballers and other football participants stick to religion to prepare themselves psychologically aside their physical skills and exertion. Iona & Okou, in their study titled "Sports and Religion" state that sportsmen (including footballers) can use their religion as a source of psychological support as they cope with the challenges and uncertainties of competition and as they try to find special meaning for their sports lives [40]. Religious rituals help footballers to overcome anxieties and excessive environmental stimuli, such as chanting of fans, from interrupting their concentration.…”
Section: Psychological Supportmentioning
confidence: 99%
“…They see prayer perhaps to be the most frequently employed use of religion by footballers [42]. Slatinsky et al also found that footballers with a greater internal locus of control and higher strength of religious beliefs had a higher level of resiliency than players with a high external locus of control and lower strength of religious beliefs [43]. Eric Bekoe posits that his motivation, psychological and spiritual support in the success of any match he plays come from the Psalm 91.…”
Section: Psychological Supportmentioning
confidence: 99%